Project Based Learning: Strategi Pelaksanaan Praktikum IPA SD Dimasa Pandemi Covid-19 - I Made Ari Winangun (STAHN Mpu Kuturan Singaraja, 2021)
The Covid-19 pandemic has revolutionized the learning implementation system which was initially implemented face-to-face and turned into online learning. The strategy for implementing science practicum in elementary schools in this study is carried out by applying an innovative learning model, namely project based learning with a scientific approach that is able to develop 21st century learning skills, namely critical thinking, communication, collaboration, and creativity. Examples of the implementation of elementary science practicum with the application of project based learning, namely the content of elementary school science lessons in class V semester II, Theme 7 (Events in Life), Sub-theme 1 (National Events of the Colonial Period), in learning 1, 2 and 5. The strategy for implementing natural science practicum in elementary schools is expected to be able to increase student interest, skills, and independence in learning and reduce student boredom in online learning which seems monotonous.Keywords: project based learning, science practicum in elementary schools